Video-nystagmography test findings in post COVID-19 patients. (8th August 2021) - Abdelrahman, Tayseer Taha; Shafik, Noha Ali
Abstract: Objectives: There is growing evidence of neurological involvement of SARS-CoV-2 in some otoneurological subjective symptoms such as balance disorders. The aim of this work was to investigate the prevalence of equilibrium disorders such as dizziness and vertigo in a sample of COVID-19 patients after recovery. The effect of COVID-19 on the vestibular system and the correlation between the severity of the infection and the effect on the vestibular system was investigated. Methods: Twenty Post COVID-19 subjects after complete cure who complain of dizziness were subjected to full history taking, Otological examination, Pure tone audiometry, and Videonystagmography test. Results: Half of the patients have a history of the sense of imbalance attacks and most patients showed positional nystagmus followed by caloric weakness. Half of the patients that had a history of severe COVID-19 disease have a symmetrical caloric response. However, two-thirds with a history of either mild or moderate degree COVID-19 had asymmetrical caloric response with a significant difference between the incidence in severe versus mild and moderate degrees reflecting a significant association between the severity of the disease and the caloric asymmetry. Conclusion: The SARS-CoV-2 virus can affect different parts of the vestibular system.